Analysis of the Impact of Panoramic Train Ticket Prices on Argo Parahyangan Passenger Satisfaction - Suryono, Totok; Mulyani, Haniva; Kartika, Ananda Putri (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to analyze the effect of Panoramic Train ticket prices on customer satisfaction in the relationship between Argo Parahyangan Gambir-Bandung Train and PT Kereta Api Pariwisata. A quantitative approach was applied by collecting data through questionnaires distributed to 100 passengers. The results of the study indicate that ticket prices that are in accordance with service quality have a significant effect on customer satisfaction. Appropriate pricing can increase satisfaction, while good quality service contributes to a satisfying travel experience. Factors such as comfort, cleanliness, and staff service also affect passenger perceptions of the services provided. This study provides useful insights for PT Kereta Api Pariwisata in optimizing pricing strategies and improving service quality. By understanding the relationship between ticket prices and customer satisfaction, companies can maintain and improve customer satisfaction, which ultimately increases loyalty and corporate image. Therefore, it is important for companies to adjust ticket prices to customer expectations and continue to improve service standards to maintain a competitive position in the transportation market.